Pemodelan Matematis dari Sifat Fisis Aliran Fluida pada Saluran Pipa Menggunakan Metode Beda Hingga 2 Dimensi - Aurista Miftahatul Ilmah (POLITEKNIK NEGERI BENGKALIS, 2021)
The piping system is used as a fluid transfer that is in the form of gas or liquid. In fluid flow it depends on pressure and velocity. Mathematical depiction of fluid can be seen from a straight line pattern. These patterns will form a corresponding flow nets. As a depiction of fluid flow in accordance with the shape of the pipe in the piping system and its velocity, it can be done by several methods, one of which is the finite difference method, this method includes mathematical and physical methods, where mathematical modeling can explain the physical properties of a fluid in a pipe. From this research, two variations of pipe shape were obtained, namely the straight pipe shape and the widening pipe shape, from the results obtained. That the fluid flow equation can be visualized in a mathematical way from the physical equation in a fluid.